The last lawyer : the fight to save death row inmates - Temple, John, 1969- (Book collections on Project MUSE., 2009)
The Last Lawyer is the true, inside story of how an idealistic legal genius and his diverse band of investigators and fellow attorneys fought to overturn a client?s final sentence. Ken Rose has handled more capital appeals cases than almost any other attorney in the United States. The Last Lawyer chronicles Rose's decade-long defense of Bo Jones, a North Carolina farmhand convicted of a 1987 murder. Rose called this his most frustrating case in twenty-five years, and it was one that received scant attention from judges or journalists. The Jones case bares the thorniest issues surrounding capit.